Staphylococcus aureus-induced pyogranulomatous dermatitis, osteomyelitis, and meningitis with Splendore-Hoeppli reaction in a cat coinfected with the feline leukemia virus and Leishmania sp. - Carvalho, Thaynara Parente de; Eckstein, Camila; Moura, Larissa Layara de; Heleno, Nathália Von Ruckert; Silva, Laice Alves da; Santos, Daniel Oliveira dos; Souza, Lucas dos Reis de; Oliveira, Ayisa Rodrigues; Xavier, Rafael Gariglio Clark; Thompson, Mayerson; Silva, Rodrigo Otavio Silveira; Santos, Renato Lima (Brazilian Journal of Veterinary Pathology, 2022)
This report describes a case of a pyogranulomatous dermatitis, osteomyelitis, and meningitis with Splendore-Hoeppli reaction caused by Staphylococcus aureus in a sheltered female adult cat coinfected with the feline leukemia virus (FeLV) and Leishmania sp. The cat had a mild anemia and marked increased total leukocytes, particularly band and segmented neutrophils. The cat had laboratorial diagnosis of FeLV and Leishmania sp. infections. Clinically, the cat had extensive and multifocal areas of ulceration in cranial region. Due to the progression of cutaneous lesions, progressive weight loss, and the risk for other sheltered animals, the cat was euthanized. Microscopically, there was marked pyogranulomatous ulcerative dermatitis, osteomyelitis and meningitis, with multiple large intralesional colonies of Gram-positive cocci associated with Splendore-Hoeppli reaction. Aerobic bacterial isolates were identified as S. aureus by MALDI-ToF MS. Leishmania sp. DNA sequences were detected in liver and spleen, and amastigotes were demonstrated in skin sections by immunohistochemistry. In conclusion, here we describe a case of S. aureus-induced pyogranulomatous meningitis with SH reaction in a cat naturally coinfected with FeLV and Leishmania sp.